Custom 3D-printed split-type triflange implants for severe acetabular defects: mid-term clinical outcomes and biomechanical insights from finite element analysis - Guo, Yu; Feng, Dehong; Gu, Xiaofeng; Wang, Ling; Ding, Yujian; Liu, Yi; Qin, Jialin (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundPaprosky 3B acetabular defects challenge revision total hip arthroplasty (THA) due to conventional techniques’ high failure rates. This study evaluates midterm outcomes and biomechanical performance of 3D-printed split-type triflange acetabular cups for Paprosky 3B defects.Materials and methodsFrom 02/01/2017 to 10/30/2021, we retrospectively assessed 14 patients with Paprosky 3B defects using 3D-printed split-type triflange cups. Preoperative CT-based 3D models guided implant design with porous surfaces and optimized screw fixation. Clinical outcomes were assessed via Harris Hip Score (HHS) and Oxford Hip Score (OHS). Radiographic parameters and implant stability were analyzed. Biomechanical characteristics were evaluated through finite element analysis (FEA) under physiological loads representing single-leg stance, walking, and jogging (700N, 2800N, and 4200N).ResultsAt mean 74.2-month follow-up, HHS improved from 31.9 ± 8.5 to 82.9 ± 5.9 (p < 0.05) and OHS from 7.6 ± 2.3 to 35.4 ± 3.1 (p < 0.05). Anatomical hip center restoration was achieved with comparable postoperative and contralateral rotation center measurements. Radiographic analysis confirmed stable fixation in all cases without loosening. FEA revealed distinct biomechanical behavior between bone models. In both normal and osteoporotic models, stress concentrated at the superior flange screw fixation site and the superior acetabular rim. Under 700N loading, interfacial micromotion at all measurement points (P1-P3) remained below the 40 μm threshold for osseointegration. However, at higher loads (2800N and 4200N), P1 micromotion significantly exceeded this critical threshold in both models, reaching 122.861 μm and 131.244 μm respectively at maximum loading, while P2 and P3 maintained acceptable levels.ConclusionCustom 3D-printed split-type triflange prostheses achieve excellent midterm functional restoration and biomechanical stability in Paprosky 3B defects. Key advantages include precise hip rotation center reconstruction, favorable stress distribution, and reduced intraoperative morbidity. Early partial weight-bearing is safe, though high-impact activities should await radiographic confirmation of osseointegration. Long-term validation of durability is warranted.